Care of Elephants - Chaturvedi, M. D. (Indian Forester, 1950)
Atomized kerosene has proved far more effective in dealing with maggots in wounds of animals than chemicals. While oil soothes the wound and stifles maggots to death, chemicals kill the living tissue far more than maggots.